PERLINDUNGAN HUKUM TANAH WAKAF YANG TIDAK MEMILIKI AKTA IKRAR WAKAF - Rachmat Taibu; Ulfa Novrianti (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2023)
This study aims to determine and examine the rights to waqf land that does not have a waqf pledge and its position at the Baubau City Land Office and Baubau City Religious Affairs Office.This research was carried out at the Baubau City Land Office and Baubau Religious Affairs Office, the method used in this research is normative legal research that examines positive law and legal principles and their theoretical aspects through reading sources, such as laws, books, articles scientific, mass media, and legal journals and in this case the researchers obtained data directly from the parties concerned which were specifically collected for this research by conducting direct interviews. The results show that based on legal efforts to protect the rights of waqf that do not have the status of waqf land without a waqf pledge that occurs in Baubau City is if the waqf element is not fulfilled, then legally the waqf can be said to never exist. The making of the Waqf Pledge Deed has a very important meaning, because by making the waqf pledge deed, the endowment will be authentically proven and so that it can be judged whether or not a legal event is true and the evidence for the waqf pledge is legal evidence.